Recent advances and future directions on GLA-producing organisms - Latifi, Mojgan; Jalali Bidgoli, Foroozan; Hajihassani, Helia; Hassani, Danial; Ingvarsson, Pär K.; Farrokhi, Naser (Frontiers in Bioengineering and Biotechnology, 2025)
Gamma-linolenic acid (GLA) is a biologically active omega-6 fatty acid with anti-inflammatory, immunomodulatory, and cardiovascular protective effects. It is a vital constituent of human health and is finding more widespread applications in nutritional supplements, medications, and functional foods. GLA can be derived from many different natural sources, including plants, fungi, and microorganisms. This review paper presents an overview of the current advances in the discovery, metabolic engineering, and GLA-producing organism optimization. We further present a discussion on new biotechnological approaches—such as culture medium optimization, genetic engineering, and genome editing—that can be employed to enhance GLA production. The paper also presents new trends and directions in the commercial exploitation of GLA-containing products, unveiling new, health-oriented applications.